DIRECTIONS FOR IMPROVING THE ENFORCEMENT MECHANISM OF THE FOOD MARKET - Sotvoldiev Nodirbek Jurabaevich (Scholars Digest Publishing, 2023)
The article reveals the domestic possibilities of food production. A set of measures to be implemented in the Fergana region has been developed to achieve the strategic indicators of agricultural development of the Republic of Uzbekistan for 2020-2030. A scientific proposal and practical recommendations aimed at improving the regional food market are given.
Keywords: region, Fergana region, food market, agriculture, strategic indicators, program, stage, internal market, specialization.